Potret Pembelajaran Daring LATSAR CPNS Angkatan 19 pada Masa Pandemi Covid 19 di Lingkungan PPSDMA KESDM - Helmi, Ahmad; Choiruddin, Irfan (JURNAL APARATUR, 2021)
ABSTRACT This study aims to analyze Whole of Government learning subject through online classes at Latsar CPNS, a cooperation program of the Ministry of Education and Culture's Employees Education and Training Center with Ministry of Energy and Mineral Resources PPSDM Aparatur during the COVID-19 pandemic at PPSDM Aparatur. Qualitative research methods were selected with a quasi-experimental analysis approach. The results of the study were as follow: the result of the class average post test score was 95.6 or very satisfying, the highest score per participant was 100 or very satisfying and the lowest was 81 or satisfactory. The advantage of online learning is the increase in participants' understanding of WOG learning materials and classes that are not boring. The drawbacks are the lack of understanding of the participants, time management and non-multiple choice tests. Suggestions for improvement are to increase the discussion of learning material, replace essays questions with with multiple choice questions, and increase the number and variety of questions. In general, online learning was considered positive and effective by participants so that it could be continued both during the pandemic and after the pandemic period ended normally.  ABSTRAK Penelitian ini bertujuan menganalisis pembelajaran Whole of Government melalui kelas daring pada Latsar CPNS Kerjasama Pusdiklat Pegawai Kemendikbud dengan PPSDM Aparatur, Kementerian ESDM dalam masa pandemi COVID-19 di PPSDM Aparatur. Metode penelitian kualitatif dipilih dengan pendekatan analisa kuasi ekperimen. Hasil penelitian adalah sebagai berikut: hasil nilai post-test rata-rata kelas adalah 95,6 atau sangat memuaskan, nilai per peserta tertinggi dengan nilai 100 atau sangat memuaskan dan terendah 81 atau memuaskan. Kelebihan dari pembelajaran daring adalah meningkatnya pemahaman peserta terhadap materi pembelajaran WOG dan kelas yang tidak membosankan. Kekurangannya adalah pemahaman peserta yang kurang, manajemen waktu dan tes non pilihan ganda. Saran perbaikan adalah menambah pembahasan materi pembelajaran, bentuk soal dengan esai diganti dengan soal pilihan ganda, dan menambah jumlah dan variasi soal. Secara umum pembelajaran daring dinilai positif dan efektif oleh peserta sehingga dapat dilanjutkan baik pada masa pandemi maupun setelah masa pandemi ini berakhir normal.